Islamic Banks Between the Jurisprudence of Leading Theorists and Application - Abdalrahman Mohamad Migdad; Ashraf Dawaba (University of Darussalam Gontor, 2022)
The last half of the twentieth century witnessed the birth of Islamic banks. Since their inception, these banks have announced - through their theoreticians - their intention to achieve economic and social development based on their commitment to the principles and provisions of Islamic Sharia. The theoreticians' interests were towards long-term investment and partnership-based contracts as a foundation for mobilizing and using financial resources to achieve development. The paper studies the performance of Islamic banks by collecting data from six Islamic banks in six of the major Muslim countries that engage in Islamic finance. Some of the main conclusions are as follows: The Islamic banks' practice reveals that the thoughts of leading theorists have become absent, as these banks have shifted from the long-term investment method to the short-term commercial method in search of liquidity and profitability. As a result, Murabaha became an alternative to credit on the output side. In turn, current deposits dominated the input side, thus transforming Islamic banks into a form similar to commercial banks. The matter was made worse by the resorting of some Islamic banks to the application of organized 'tawarruq,' which reflects the tendency of some current theorists and implementers to follow the path of traditional banks and enter the tunnel of the jurisprudence of reprehensible tricks. Also, the social role hoped for by Islamic banks has become closer to stagnation than to hoped-for mobility. Keywords; Islamic Banks, Muslim Theorists, Islamic Jurisprudence, Bank Practice, Financial Facilities